The effects of therapeutic exercises on pain, muscle strength, functional capacity, balance and hemodynamic parameters in knee osteoarthritis patients: a randomized controlled study of supervised versus home exercises - ACAR, GÖNÜL; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN; AYDOĞDU, ONUR; KURU ÇOLAK, TUĞBA; SARI, ZÜBEYİR (SPRINGER HEIDELBERG, 2017)
The aim of the study was to compare the effects of low-intensity exercise programs for lower extremities, either supervised or at home, on pain, muscle strength, balance and the hemodynamic parameters of knee osteoarthritis (OA) patients. This randomized study included 78 patients with knee OA in 2 groups of supervised and home-based exercise program. Exercises were applied to the first group in the clinic as a group exercise program and were demonstrated to the second group to be performed at home. Before and after the 6-week exercise program, assessment was made of pain, quadriceps and hamstring muscle strengths, 6-min walk test (6MWT), and non-invasive hemodynamic parameters. Results of the 78 patients, 56 completed the study. Pain, muscle strength, and 6MWT scores showed significant improvements in both groups. There were also significant differences in the amount of change in pain and muscle strength (pain: p = 0.041, Rqdc: 0.009, Lqdc: 0.013, Rhms: 0.04) which indicated greater improvements in the supervised group. The balance scores of supervised group showed a significant improvement (p = 0.009). No significant change was determined in hemodynamic parameters of either group. Conclusion according to the results of this study showed that low-intensity lower extremity exercises conducted in a clinic under the supervision of a physiotherapist were more effective than home-based exercises in reducing post-activity pain levels and improving quadriceps and right hamstring muscle strength. Both the supervised and home exercise programs were seen to be effective in reducing rest pain and increasing 6 MW distance in knee osteoarthritis patients.
Keywords: Knee; Osteoarthritis; Exercise; Balance; Pain; Functional exercise capacity; PHYSICAL INACTIVITY; QUADRICEPS WEAKNESS; SYMPTOMATIC KNEE; CARDIAC-OUTPUT; DISABILITY; ARTHRITIS; PREVALENCE; MANAGEMENT; IMPACT; WOMEN